Study on the efficiency of small-scale wind turbine with rotor adapted for low wind speeds - Strojny, Piotr (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
This article aims to present the results of tunnel tests and field tests of small-scale horizontal-axis wind turbines. The article proposes a new concept of turbine rotor adapted to improve efficiency at low wind speeds. The methodology for calculating the rotor and generator is shown. The turbine construction solution is presented briefly, along with the technology for manufacturing turbine components and assembly. An analysis of the obtained results is also conducted.